How Can the Formulation of Seventh Graders' Own Word Problems in a CBI Mathematics Class Improve Their Syntactic Linguistic Competence in a Private EFL Context? (2019)
ABSTRACT: This action research was aimed at improving seventh graders’ syntactic competence in a Content Based Instruction mathematics class through the formulation of word problems at a private institution in Medellin, Colombia. Data were collected through a journal, some students’ papers, a questionnaire to students, and three peer teacher observations. Data analysis showed some improvement at a syntactic and grammatical level; surprisingly, the most significant improvement was in the lexical and semantic components. Moreover, the students’ comprehension for problem solving as well as the application of several strategies for formulating and solving problems improved. Additionally, their confidence to approach mathematics as a field increased. The application of this strategy would be interesting and useful with elementary school children at long term.